Sexo no mercado produção de verdades, desejos e moral - Carvalho, Eliane Knorr de (2017)
Sex enrobed in sexuality has become a lucrative business. It has opened the way for investments in people as human capital through discussions based on health and religion. The objective of this work is to present how the reappraisal of sexuality – based on the concept of dispositif as defined by Michel Foucault – facilitated by the modulation and accommodation of practices considered as subversive in rights that are negotiable within the market. Thus, the range of investments in the normalized population's behavior was broadened. The production of comprehensive concepts related to sexual health – in partnership between State, religion and international organizations – enabled investments in calculating a mortified life. This work is presented in three series. The first serie, entitled "games of truth (production of identities, rights and education in the field of sexuality)" focuses on the United States and San Francisco Bay Area. It presents some of the disputes over truths around identities; the production of knowledges in the light of these truths; market negotiations and the relationship between education; and investment in human capital. In the second serie, "productions of desires (new investments in the sex market in Brazil)", the Erótika Fair, in São Paulo, presents itself as a profitable field for the analysis of the production and assimilation of desires, justified by the introduction of the female audience into this market. The analysis situates the assimilation of concepts within the marketplace that translates the personal relationships into business and takes these businesses into the personal field. Finally, "sexual morality (religion and health)," highlights the investments of Christian churches in the guidance of behavior, focusing on the analysis of evangelical groups, and their articulation within international guidelines on sexual health. And how the HIV/AIDS context is used to justify education programs for children and young people, of a calculated life, in which they abdicate so-called deviations in the present in the name of the promise of a better future